1994
DOI: 10.1002/jmv.1890420108
|View full text |Cite
|
Sign up to set email alerts
|

Blood in saliva of patients with acquired immunodeficiency syndrome: Possible implication in sexual transmission of the disease

Abstract: The presence and concentration of haemoglobin in saliva of anti-human immunodeficiency virus (HIV) positive subjects, anti-HIV-negative subjects at high risk of infection, and healthy controls were studied. One hundred eighty-eight subjects were anti-HIV-positive intravenous drug abusers (IVDA), 22 were anti-HIV-positive homosexual men, 23 were anti-HIV-positive heterosexual contacts, 132 were anti-HIV-negative IVDA, 35 were anti-HIV-negative homosexual men, and 154 were healthy controls. Two milliliters of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Piazza et al (1989Piazza et al ( , 1994 showed that blood was present in the saliva of 50% of healthy subjects without visible lesions of the oral mucosa and in the saliva of 65.7% of HIV-1-seropositive subjects. There was no significant correlation between the detection of blood and cell-associated HIV-1 in GCF samples from the HIV-1seropositive patients examined.…”
Section: Discussionmentioning
confidence: 99%
“…Piazza et al (1989Piazza et al ( , 1994 showed that blood was present in the saliva of 50% of healthy subjects without visible lesions of the oral mucosa and in the saliva of 65.7% of HIV-1-seropositive subjects. There was no significant correlation between the detection of blood and cell-associated HIV-1 in GCF samples from the HIV-1seropositive patients examined.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of salivary anti-HIV-1 immunoglobulin A antibodies that occurs during symptomatic HIV-1 infection (12, 17) is not expected to affect the sensitivity of TestPack because the secondary antibody used is specific for human immunoglobulin G according to the package insert (Abbott Laboratories). The hemoglobin concentration in saliva has been found to be higher in HIV-1-infected patients with low circulating counts of CD4 lymphocytes (14) probably because of frank bleeding from HIV-1-related oral pathology, such as candida stomatitis and aphthous ulcers. Transudation of serum or frank bleeding into the oral cavity would be expected to increase the concentration of immunoglobulin G in saliva (9) and probably accounts for our observation of increased sensitivity of saliva antibody testing in more-symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…HIV can indeed be isolated from saliva, but infrequently. 180 Saliva may of course, also contain blood 181 and it has been suggested that HIV may be transmitted after deep kissing, 182 especially if there is blood in the mouth. 183 Hemoglobin concentrations in saliva are higher in HIVpositive intravenous drug abusers (IVDA) than in HIV-negative IVDA and controls, and in AIDS a mean of 1.3 µL blood/mL saliva has been estimated.…”
Section: Human Immunodeficiency Viruses (Hiv)mentioning
confidence: 99%